Literature Review: Storybook Media Improves Reading Understanding of Montessori Theory for Class V Elementary School - Azis, Moch Qitfirul; Sukartiningsi, Wahyu; Subrata, Heru; Adri, Helmia Tasti (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
In learning Indonesian, we found problems that occurred in fifth grade elementary school as follows: 1) generally the learning media was not in accordance with the characteristics of the students, 2) some students used learning media that were not suitable for learning Indonesian, 3) students were less interested in reading because of the media reading is not interesting for students. This will affect the ability to understand the main idea. The method used in writing this article is a literature review study. In 4 international and 6 national articles, the obstacles found with learning media were difficulties with interest in improving reading comprehension skills, while several positive things were found to increase student motivation in using book media. Stories in the learning process of students in class V elementary school. Learning media using story books is a new habit with various ways to carry out a good and interesting learning process and in accordance with curriculum objectives. Obstacles were found both psychologically and socially among fifth grade elementary school students